Toward an Alternative Research Paradigm for Small/Rural Schools: Beyond an Approximated Reality - Russel L. Dobson; Judith E. Dobson (Journal of Research in Rural Education, 1990)
This paper, based in part on the work of Thomas Kuhn, argues that most research efforts relative to rural/small schools are based in "normal science" which means research firmly based upon previous scientific achievements; a kind of stockpiling of knowledge, that supplies the foundation for further practice. This preconceived reality of researchers attempts to force the nature of rural/small schools into a relatively inflexible box. A case is presented that at best this body of knowledge represents an approximated reality.